QUALITY CONTROL AND PRODUCTIVITY OF METAL CRAFT PRODUCTS IN PASIR MUKTI VILLAGE, CITEUREP DISTRICT, BOGOR REGENCY - Shinta Aminda, Renea; Suharti, Titing; Kartika Rinda, Rachmatullaily; Surend Mahmud, Khalishah (LPPM Univ. Ibn Khaldun Bogor, 2022)
Metal products are one of the superior products of Bogor Regency, which is located in Pasirmukti Village, Sukahati, and Tarikolot, Citeureup District. The local government of Bogor Regency has made the icons in these villages a thematic village that will be used as an integrated training center for marketing the products of the metal and body industry. The area of ​​Citereup District is because the area has also produced metal industries since the 1980s, and has survived to this day, Micro, Small and Medium Enterprises (MSMEs) are the main supporter of the economy of the residents of Citeureup District.